Stop codon recognition in ciliates: Euplotes release factor does not respond to reassigned UGA codon - Kervestin, Stéphanie (Oxford University Press, 2001)
In eukaryotes, the polypeptide release factor 1 (eRF1) is involved in translation termination at all three stop codons. However, the mechanism for decoding stop codons remains unknown. A direct interaction of eRF1 with the stop codons has been postulated. Recent studies focus on eRF1 from ciliates in which some stop codons are reassigned to sense codons. Using an in vitro assay based on mammalian ribosomes, we show that eRF1 from the ciliate Euplotes aediculatus responds to UAA and UAG as stop codons and lacks the capacity to decipher the UGA codon, which encodes cysteine in this organism. This result strongly suggests that in ciliates with variant genetic codes eRF1 does not recognize the reassigned codons. Recent hypotheses describing stop codon discrimination by eRF1 are not fully consistent with the set of eRF1 sequences available so far and require direct experimental testing.